Прогнозування неплатоспроможності малого будівельного підприємства за допомогою дискримінантного аналізу - Антропов, Ю. В. (Ways to Improve Construction Efficiency, 2012)
Application of discriminant analysis helped identify the key factors that can help you with a high degree of probability to predict the problems of finance of small construction company. An appropriate model.